Executive Presidency and Intra-Institutional Crisis in Nigeria, 1999 - 2015 (Global Journal of Human-Social Science, 2016)
Many federal systems incorporate presidential system with individual or dual executive Such executive presidencies are imbued with substantial powers dominating politics and government with farreaching implications The potential advantage of presidential system is often challenged by the occurrence of divided governments capable of thwarting executive s potential successes Recurringintrainstitutionalleadership crisis borne out of high-wired politics personal and political differences negating the spirit of the Constitution and threatening democratic consolidation suffice Such crisis underlines the limitations of individual and dual executives amidst agitations for amendment to perceived flaws in constitutional provisions in emerging democracies The Nigeria s 1999 Constitution provides for dual executive presidency comprising a President and a Vice-President jointly elected for a renewable fouryear term of office The predominance of viable governing institutions as opposed to personal leadership was an aberration prior to the embrace of popular government
Keywords: nigeria; executive presidency; intrainstitutional; crisis; and power